Differences in the explosive strength of lower limbs during the performance of basketball jump shot - Radenkovic, M.; Stankovic, R.; Stojic, M.; Paunovic, M. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The aim of this study was to determine the difference in explosive strength of lower limbs during the performance of basketball jump shots by youth basketball players. Participants were 64 basketball players, divided into two groups, experimental with 32 players (age 15.41 +/- 0.33), and control with 32 players (age 15.9 +/- 0.11). For determining the differences between groups on initial and on final measurement t-test for independent samples was used. The results showed that on the initial measurement there was a difference between the two variables and that on final measurement, after 10 weeks of the training program, there was the difference in eight variables.